An Empirical Study on Factors Influencing Job Satisfaction of Human Resource in Bank and Insurance Companies of Nepal (Global Journal of Management and Business Research, 2023)
Job satisfaction is the positive emotional feeling of an employee towards their job It is one of the most important outcomes of an organization depends on the various motivational factors Out of different motivational theories this research work has used Herzberg s Two Factor Theory of motivation to understand the impact of motivational factors on job satisfaction of human resource working in bank and insurance companies of Nepal Due to the use of the theory the assumed 15 motivational factors are classified into two groups- i e hygiene factor and motivator factor and later on each of the motivational factors are further grouped into motivational and de-motivation factors to meet the assumption of independent sample t-test through IBM SPSS 25 version To test the internal consistency reliability of questions related to 15 constructs the Cronbach Alfa coefficient has been calculated To create consistency with the sample size assumed in Herzberg s theory of motivation this research paper has collected primary data from 200 respondents through a face-to-face interview method with a structured questionnaire Results of this research work have partially accepted the conclusion of Herzberg s theory of motivation The development of the independent sample t-test it has been found that relation with colleagues and allowances do not significantly affect on the level of job satisfaction of human resources whereas the remaining 13 motivational factors- i e salary bonus vehicle facility training job promotion work environment rules regulations loan facility relation with superior awards challenging job relation with subordinate and job security do significantly effect on job satisfaction of human resources The research paper concludes that to improve the job satisfaction of human resource the bank and insurance companies of Nepal should increase their time effort and finance on the remaining 13 motivational factors rather than on the two motivational factors
Keywords: job satisfaction; herzberg’s two factor theory; bank; insurance companies; human resources; motivational factors; Nepal